The outcome of acute leukemia patients with SET-NUP214 fusion after allogeneic stem cell transplantation - Shen, Yuyan; Yang, Donglin; Zhang, Rongli; Chen, Xin; Ma, Qiaoling; Wei, Jialin; Zhai, Weihua; Pang, Aiming; He, Yi; Jiang, Erlie; Feng, Sizhou (Frontiers in Oncology, 2023)
SET-NUP214 fusion gene, also known as TAF-1-CAN and SET-CAN, is observed in acute myeloid leukemia (AML) and T-cell lymphoblastic leukemia (T-ALL). SET-NUP214 fusion in T-cell lymphoblastic leukemia is associated with chemotherapy resistance, but the prognosis of patients with AML with SET-NUP214 has rarely been reported. In the present study, we retrospectively analyzed all patients with acute leukemia including AML and T-ALL patients with SET-NUP214 fusion who underwent allogeneic stem cell transplantation (alloHSCT) in our center from July 2017 to November 2022. Of the total 11 patients, 5 patients were diagnosed with AML and 6 patients were diagnosed with T-ALL de novo. All patients received myeloablative regimens in CR1, and there were three (60%) AML patients who relapsed post-alloHSCT and three T-ALL (50%) patients who relapsed post-alloHSCT. Only one patient with AML who relapsed post-alloHSCT responded to subsequent chemotherapy plus donor lymphocyte infusion and survived the last follow-up. The estimated 1-year overall survival and 3-year overall survival for all these 11 patients were 69.3% and 38.5%, respectively. The estimated 1-year leukemia-free survival and 3-year leukemia-free survival for all patients were 69.3% and 38.5%, respectively. The research shows a high incidence of relapse for patients with acute leukemia with the SET-NUP214 fusion gene, even after alloHSCT. More clinical trials or research with larger samples are urgently needed for this group of patients.